The Deliverance of Hadith by Khateeb in Friday Prayers from the Perspective of Hadith Science: As an Islamic Cultural Practice - Waharjani Waharjani; Mohammad Jailani; Wan Rashidah Hanim Bt Wan Mohamad; Dewi Aprilia Ningrum (Mimbar Agama dan Budaya, 2024)
Many khateeb of Friday prayer improperly quote the Prophetic hadiths; some of them, for example, just quote the matan (content) of the hadiths. Hadith comprises three elements: sanad, matan, and rawi. This study aims to analyze the use of the prophetic hadiths among when the khateeb in delivering the khutbah (sermon) during the Friday prayer. This research was conducted at a number of Jami' mosques (mosques hosting Friday noon prayers known as jumu'ah) in Yogyakarta during Friday prayer. The subject of this qualitative research is the khateeb who delivers the khutbah (sermons), which was determined by purposive sampling. The data in this study were collected through observation, interviews, and documentation and analyzed by means of analytical descriptive method.  The results of this study indicated a positive and important attitude as proven in the way of khateeb, that always quoted and delivered the hadiths as an explanation of the verses of the Qur'an, though the delivery was not as expected by hadith experts and scholars in relation to their insufficient knowledge of hadith science.